(untitled) (Research, Society and Development, 2022)
Due to the increasing number and prevalence of antibiotic-resistant microorganisms, our arsenal of antibiotics is no longer effective in controlling skin and soft tissue infections. Faced with this, many doctors and researchers begin to look back at the history of medicine, in the incessant search for alternative treatments, re-examining previous technologies with advanced tools and the wisdom of the 21st century, when faced with larval therapy. To analyze the scientific production on the use of larval therapy in the treatment of wounds. This is a scientific research of the integrative literature review type, in which it was used to generate the guiding question of this integrative literature review: “What does the scientific evidence show regarding the use of larval therapy in the treatment of wounds?” To locate the relevant studies that answered the research question, indexed and non-indexed descriptors (keywords) in Portuguese, English and Spanish were used. The results suggest that larvotherapy could have the potential to synergistically improve wound healing and result in shorter hospital stays, given the low cost of breeding worms, the technology is likely to be cost effective compared to other therapies. Finally, it is still estimated the development of more studies on the subject, deepening and improving knowledge, to strengthen the results to be obtained in the treatments.